Noise pollution and post-COVID-19 pandemic mobility: a case for ambient noise - Kumar, Mohan; Naik, Gitismita (International Journal Of Community Medicine And Public Health, 2022)
Noise as a hindrance to health is a low priority in India. The existing statutory controls for noise pollution in India are highly inadequate amidst an implementation gap and should better suit Indian culture and social set-up. Though ubiquitous in nature, community noise and industrial noise are the two major settings from where noise occurs. Exposure to noise above the threshold and over prolonged periods can lead to auditory and non-auditory effects on health; including but not limited to cardiovascular diseases, neurosis, mental illness, stomach ulcers, respiratory disorder exacerbations, sleep disturbances, fetal and maternal complications, child developmental disabilities, psychological dysfunctions/ negative social behavior, road traffic and industrial accidents. The social and economic costs associated with noise pollution are manifold. COVID-19 pandemic has forced countries worldwide to enforce lockdowns resulting in an involuntary ambient noise reduction and other ecological changes like cleaner rivers and air. To sustain the environmental ‘gains’ of enforced lockdowns, it is important for national governments and international health agencies to emphasize better implementation of rules governing pollution in addition to adopting/adapting newer proven technologies; making ‎post-COVID-19 pandemic mobility more environmentally sound, healthy ‎and sustainable. Noise pollution mitigation strategies should be worked out at city levels and having a coordinated and long-term integrated noise pollution research is the need of the hour.